EVALUASI PENGGUNAAN TOTALLY IMPLANTABLE VENOUS ACCESS PORT UNTUK KEMOTERAPI PADA PASIEN KANKER PAYUDARA DI RUMAH SAKIT UMUM PUSAT SANGLAH TAHUN 2016 - Ayu Nursantisuryani Jahya; Putu Anda Tusta Adi (Universitas Udayana, 2020)
The route of chemotherapy administration affects patient adherence and compliance. The Totally Implantable Venous Access Port (TIVAP) emerged as a promising method for optimal access to chemotherapy. However, evaluation of its usage was still low compared to its high demand. This study was conducted to determine the characteristics, indications, dan complications of TIVAP implantation in female subjects with breast cancer who underwent chemotherapy using TIVAP at RSUP Sanglah in the period of March 2015 to September 2016. This was a descriptive method with cross sectional design using secondary data from medical records of breast cancer patients visiting Sanglah General Hospital. Data on subject characteristics, indications, and complications of TIVAP were analyzed with SPSS. In this study, it was shown that TIVAP users mostly aged over 40 years with breast cancer on the left. Majority (61%) chose this method after being educated. TIVAP mostly implanted in the right subclavian vein. There were 3 out of 28 subjects (9%) who experienced complications: 1 subject (3%) had an early complication due to thrombus blocking and 2 subjects (6%) had late complications due to exposed chemoport and infection, respectively. It can be concluded that the highest indication of TIVAP usage was after education and the rate of complications was low and mild. Thus, TIVAP is a safe and good method to be applied as a route of chemotherapy administration. Keywords: breast cancer, chemotherapy, TIVAP